Dimensi Sharia Compliance Pada Operasional Bank Syariah Indonesia (BSI) - Suyuthi, Lailatun Nur; Mugiyati, Mugiyati (Jurnal Ilmiah Ekonomi Islam, 2024)
This journal discusses the dimensions of sharia compliance in the operations of Bank Syariah Indonesia (BSI) which operates based on Islamic sharia principles. Bank Syariah Indonesia (BSI) is the result of a merger of the three largest Islamic banks in Indonesia. This research uses a library study method to explore information related to sharia compliance in Islamic bank operations. The results showed that Islamic banks have a different operational system from conventional banks, focusing on justice, honesty, and ethical investment. Islamic banks must comply with Sharia principles in their operations, including no usury, gharar, maisir, and must conduct business based on halal profits. Shariah compliance in Islamic Bank operations has seven dimensions that must be adhered to. Thus, the conclusion of this journal emphasizes the importance of Shariah compliance in the operations of Islamic banks to ensure compliance with the principles of Islamic shariah and maintain customer trust.